THE REASONS AND PUNISHMENTS FOR NOT DOING HOMEWORK - Esonova Muxtasarxon Doniyor qizi; Kosimova Mukammalxon Umaraliyevna (TADQIQOTLAR.UZ, 2023)
Annotation: assigning homework to students is the requirement of teachers of all the time. This article depicts general problems the teachers face during assessing students' home tasks and ways to handle them efficiently.